Behavior of Concrete Containing Alternative Pozzolan Calcined Marl Blended Cement - Akgün, Yasemin (Periodica Polytechnica Civil Engineering, 2020)
Natural marl which is calcined at appropriate temperature has potential being alternative pozzolan. Therefore, the calcined marl is wanted to be used as replacement material in blended cements with less clinker. This situation leads to improved performance of cement/concrete, reduced CO2 emissions, saving of energy. The properties of used pozzolan positively effect to some behavior of concrete. Shrinkage is one of these properties. The shrinkage of concrete is inherent property that needs to be control. Moreover, the shrinkage of concrete becomes even more important in some applications such as mass concrete, prestressed concrete. The aim of study is to determinate how will affected shrinkage of concrete containing alternative pozzolan calcined marl blended cements. Accordingly, the natural marl was calcined at 800 °C for pozzolanic activation. The calcined marl was replaced with Portland cement at ratios of 0, 10, 30, 50 wt.%. The setting times, volume expansion, water demand, density, performance energy evaluation of blended cements were determined. The autogenous-drying shrinkage, mass loss and compressive strength tests were performed on concretes containing calcined marl blended cements. According to the results, pozzolanic activity of calcined marl and properties of blended cements containing calcined marl are comply with limit values of TS 25 and EN197-1. It was observed that autogenous-drying shrinkage and mass loss of concretes containing calcined marl blended cement were lower than that of concretes containing Portland cement. On the other hand, it was seen that compressive strength of concretes was increased up to 50 % replacement ratio.